2017
DOI: 10.1007/s00198-017-4249-z
|View full text |Cite
|
Sign up to set email alerts
|

Standards of reporting: the use of CONSORT PRO and CERT in individuals living with osteoporosis

Abstract: The Consolidated Standards of Reporting Trials for Patient-Reported Outcomes (CONSORT PRO) and the Consensus on Exercise Reporting Template (CERT) have been developed to improve the quality and transparency of reporting standards in scientific research. The purpose of this study was to provide evidence for the adoption of CONSORT PRO and CERT by researchers examining the link between exercise and quality of life in individuals living with osteoporosis. A systematic search was conducted to identify randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…For every instrument used in this study, more than half of the items on the list were reported less than 50% of the time. These results align with the findings of Hay‐Smith et al, as well as other studies that have shown poor exercise‐based intervention reporting in the physiotherapy management of pelvic floor and other conditions . This trend across the physiotherapy literature demonstrates the necessity for the systematic use of standardized instruments such as CERT and TIDieR to detail, as much as possible, all of the parameters of an exercise intervention to facilitate best practices implementation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For every instrument used in this study, more than half of the items on the list were reported less than 50% of the time. These results align with the findings of Hay‐Smith et al, as well as other studies that have shown poor exercise‐based intervention reporting in the physiotherapy management of pelvic floor and other conditions . This trend across the physiotherapy literature demonstrates the necessity for the systematic use of standardized instruments such as CERT and TIDieR to detail, as much as possible, all of the parameters of an exercise intervention to facilitate best practices implementation.…”
Section: Discussionsupporting
confidence: 88%
“…Physiotherapy is an evidence‐based science that has produced good quality research to guide treatment and clinical decision‐making. Recent studies in other areas of physiotherapy have, however, revealed gaps in reporting on exercise‐based interventions, which can lead to difficulties in reproducing the interventions in clinical settings . Indeed, Yamato et al, reported that for most physiotherapy trials, the interventions are unreproducible.…”
Section: Introductionmentioning
confidence: 99%
“…Explanation: A reader of a scientific article can be confident in its contents only if all essential elements of methodology and results were reported. There is a number of international standards agreed on by scientific societies or associations for various types of studies, including: Standards for reporting qualitative research (SRQR) ( 29 ), Consolidated Standards of Reporting Trials for Patient-Reported Outcomes (CONSORT PRO) ( 30 ), Consensus on Exercise Reporting Template (CERT) ( 30 ), Standards of Evidence for Conducting and Reporting Economic Evaluations in Prevention Science ( 31 ), REporting of studies Conducted using Observational Routinely-collected health Data (RECORD) ( 32 ), Consolidated Standards of Reporting Trials (CONSORT) ( 33 ), the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines ( 34 ), etc. Surveys of adherence to standards of reporting showed that even in highly ranked journals, like New England Journal of Medicine or Lancet, the adherence rate reached no more than 55% and 78%, respectively ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…editorial policy (eg, International Journal of Sports Physical Therapy [13]). However, systematic reviews of exercise intervention studies in diverse populations (eg, older population [10], athletes [3]) reveal that current reporting is still inadequate and does not generally adhere to the reporting guidelines.…”
Section: But Is It Reliable and Valid Evidence?mentioning
confidence: 99%